A community of communities? Emerging dynamics in the community media paradigm. (April 2015) - Ali, Christopher; Conrad, David
Recent years have seen numerous attempts by community broadcasters around the world to reinvent their practices in an effort to remain relevant and financially sustainable in the digital age. One proposed initiative is to have community programming distributed via satellite, either in the form of a single channel or as a subscription service for local stations to find programming. Combining two case studies and multiple research methods, this article investigates the potential impact of satellite distribution on community broadcasting in Canada and East Africa. We observe that it is often not the community media organizations themselves that are pushing for satellite delivery, but, rather, outside actors such as media corporations and non-governmental organizations. As a result, we argue that a more spirited discussion within the community media sector is warranted to better understand the implications of this technological shift in delivery mechanisms.